Aromatic polyphosphonates as high refractive index polymers. (February 2017) - Macdonald, Emily K.; Lacey, Joseph C.; Ogura, Ichiro; Shaver, Michael P.
Graphical abstract: Highlights: A range of polyphosphonates were synthesised through a polycondensation reaction and characterised. These samples gave good thermal properties, most being stable up to 400 °C. The glass transition temperature can be tuned by changing the end capping agent. These polymers possess the highest reported refractive index for these types of compounds. All polymers have good optical clarity in the visible region of the electromagnetic spectrum. Abstract: Highly refractive and transparent polyphosphonates with varying aromatic backbones have been synthesised by polycondensation of phosphonic dichlorides and diols, significantly expanding the reported scope of these intrinsic high refractive index polymers. The polyphosphonates display excellent thermal properties, with thermal stability up to 450 °C and tuneable glass transition temperatures ranging from 41 to 214 °C by terminating the polymer with different alcohols. The polymers synthesised also possess excellent optical properties, with low UV cut off points and high refractive indices up to 1.66, the highest reported for this type of polymer. We also report Abbe numbers for this class of polymers for the first time; all are high (>22), making these polymers excellent potential candidates for a range of optical applications.